2023
DOI: 10.1136/bmjdrc-2022-003080
|View full text |Cite
|
Sign up to set email alerts
|

How sweet is your love? Disentangling the role of marital status and quality on average glycemic levels among adults 50 years and older in the English Longitudinal Study of Ageing

Abstract: IntroductionThe health benefits of marriage have been widely documented and, to a lesser extent, the effects of marital quality. Marital relationships may be particularly relevant to the health of older adults. This study explores the associations of marital status and marital quality with average glycemic levels in older adults using longitudinal data.Research design and methodsOur sample consisted of adults aged 50–89 years without previously diagnosed diabetes from the English Longitudinal Study of Ageing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…Furthermore, a higher prevalence of diabetes mellitus type 2 was found among married participants in the present study. This is in disagreement with findings of previous studies where marriage was found to protect against type 2 diabetes mellitus [29]. Further study is needed to fully unravel the relationship between marital status and type 2 diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 93%
“…Furthermore, a higher prevalence of diabetes mellitus type 2 was found among married participants in the present study. This is in disagreement with findings of previous studies where marriage was found to protect against type 2 diabetes mellitus [29]. Further study is needed to fully unravel the relationship between marital status and type 2 diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 93%
“…Marital status appears to influence health behaviors and outcomes including glycemic control. Despite the small number of patients living without a partner in our study, similarly to other studies, [49] we found that they have higher A1C values compared to those who were married or living with a partner.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, living alone, rather than other forms of cohabitation, substantially increased the likelihood of experiencing multiple episodes of DKA (OR 2.7, 95% CI 1.09 to 6.66). It has been reported that being married is associated with lower HbA1c levels, 19 which may explain in part also a lowered risk of DKA, but data on marital status or cohabitation on DKA risk are lacking and our findings need further investigation.…”
Section: Discussionmentioning
confidence: 72%